Epileptic Seizures After Allogeneic Hematopoietic Stem Cell Transplantation - Wang, Zhuo; Zhao, Munan; Gao, Sujun (Frontiers in Neurology, 2021)
Technique in allogeneic hematopoietic stem cell transplantation has greatly advanced over the past decades, which has led to an increase in the number of patients receiving transplantation, but the complex procedure places these transplant recipients at high risk of a large spectrum of complications including neurologic involvement. As a common manifestation of neurological disorders, epileptic seizures after transplantation have been of great concern to clinicians because it seriously affects the survival rate and living quality of those recipients. The aim of this review is to elucidate the incidence of seizures after allogeneic hematopoietic stem cell transplantation, and to further summarize in detail its etiologies, possible mechanisms, clinical manifestations, therapeutic schedule, and prognosis, hoping to improve doctors' understandings of concurrent seizures following transplantation, so they can prevent, process, and eventually improve the survival and outlook for patients in a timely manner and correctly.